ANALYSIS ON DISCREPANCY CONDUCTIVITY DATA MEASUREMENT AMONG ONLINE ANALYZER AND LABORATORY - Rahmat Sabani; Dendhy Indra Wijaya (Industry Xplore, 2024)
XYZ.Co.Ltd as one Oil and Gas Company where on need steam which produced by Boiler to support of production system operational , Conductivity of Boiler Feed Water (BFW) which generated by Mix Bed Filter (MBF) have been controlling by Online Analyzer and Laboratory. Beginning from 01 April 2017 has happened data discrepancy between Online Data Result against Laboratory Result. Gap Analysis have done to determine of Desire Situation / Goal, and Goal of Research is mitigate of difference conductivity value which resulted by Online Analyzer against Laboratory. Then, Root Cause Analysis uses Ishikawa Diagram to observe root cause of the problem with several action plans to do. Ishikawa Diagram analysis uses to Root Cause Analysis resulted 1 (one) Non-Conformity has found in Machine Factor is Three Level Calibration of Conductivity Meter in Online Analyzer, because after did Chi-Square test to hypothesize of data which is generated of X2calc > X2crit as rejected and this Root Cause Analysis result has reported to Online Analyzer Section to do some Corrective Action then after Corrective action there is no discrepancy data’s anymore. Keywords: Conductivity; Online Analyzer; Laboratory; Ishikawa Abstrak XYZ.Co.Ltd sebagai salah satu Perusahaan Migas yang membutuhkan steam yang dihasilkan oleh Boiler untuk menunjang operasional sistem produksi, Konduktivitas Boiler Feed Water (BFW) yang dihasilkan oleh Mix Bed Filter (MBF) telah dikontrol oleh Online Analyzer dan Laboratorium. Mulai tanggal 01 April 2017 telah terjadi ketidaksesuaian data antara Hasil Data Online dengan Hasil Laboratorium. Gap Analysis dilakukan untuk menentukan Situasi/Tujuan yang Diinginkan, dan Tujuan Penelitian adalah memitigasi perbedaan nilai konduktivitas yang dihasilkan oleh Online Analyzer terhadap Laboratorium. Kemudian dilakukan Root Cause Analysis menggunakan Diagram Ishikawa untuk mengetahui akar permasalahan dan beberapa rencana tindakan yang harus dilakukan. Diagram Ishikawayang digunakan Root Cause Analysis menghasilkan 1 (satu) Non-Conformity yang ditemukan pada Faktor Mesin yaitu Kalibrasi Tiga Tingkat Conductivity Meter pada Online Analyzer, karena setelah dilakukan uji Chi-Square untuk menghipotesiskan data yang menghasilkan X2calc > X2crit ditolak dan hasil RoottCause Analysis dilaporkan untuk dilakukan tindakan perbaikan pada online analyzer dan setelah dilakukan perbaikan maka perbedaan hasil pengukuran tidak terjadi lagi. Kata Kunci: Konduktivitas; Online Analyzer; Laboratorium; Ishikawa